Pengaruh Kualitas Pelayanan, Nilai Pelanggan dan Citra Merek Terhadap Keputusan Pembelian pada Nadira Hijab Yogyakarta - Baiq Nurhidayati; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the effect of service quality, customer value and brand image on purchasing decisions. This study took samples who had purchased Nadira Hijab products using a quantitative method. Data collection was carried out using a Google form and the amount of data processed was 66 respondents. The research data were analyzed using multiple linear analysis and the processing was carried out using SPSS version 25. The results of this study indicate that service quality and brand image have a positive effect on purchasing decisions at Nadira Hijab Yogyakarta. Meanwhile, customer value has no positive effect on purchasing decisions at Nadira Hijab Yogyakarta.